Cross-Flow Turbine Design of Micro hydro Power Generator for Rural Energy-Independent Area - Remon Lapisa; Arwizet Karudin; Krismadinata Krismadinata; Prima Yane Putri; Junil Adri; Firman Omni Saputra; Doni Saputra; Aldi Alfarizi (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2023)
This study aims to design a cross-flow turbine in a micro hydro power plant as an alternative energy source for Indonesian remote areas that do not have electricity. The research location for the turbine design in this study is in the Ngalau Baribuik, located in Batu Gadang, Lubuk Kilangan district, Padang city. Based on the analysis of water flow characteristics, the type of turbine that is suitable for low water debit and head condition is cross flow turbine. The geometry of the cross-flow turbine is designed by considering the power electricity needs of the community and the electrical potential at the site. This experimental research was carried out in two stages; field investigations related to water flow characteristics and energy need analysis of local communities, the design and manufacture of the turbine. Based on theoretical calculation, the cross-flow turbine can produce up to 5 kW of electrical power which can meet 70% of the community's energy needs. Penelitian ini bertujuan untuk merancang sebuah turbin aliran silang pada Pembangkit Listrik Tenaga Mikro Hidro (PLTMH) sebagai alternatif sumber energi bagi daerah terisolir yang belum teraliri listrik. PLTMH dirancang untuk masyarakat kawasan Ngalau Baribuik yang berlokasi di Batu Gadang Lubuk Kilangan kota Padang. Berdasarkan analisis karakteristik aliran, untuk kondisi debit dan tinggi jatuh air yang kecil turbin yang paling sesuai digunakan adalah aliran silang. Disain dan geometri turbin disesuaikan dengan kebutuhan masyarakat dan potensi yang ada di lokasi. Penelitian eksperimen ini dilaksanakan dalam dua tahap; (a) investigasi lapangan terkait dengan karakteristik aliran air dan kebutuhan energi masyarakat, dan (b) proses perancangan dan pembuatan turbin. Secara teoritis, turbin aliran silang yang dirancang akan dapat memproduksi daya listrik hingga 5 kW yang akan memasok 25% kebutuhan energi masyarakat setempat.